Microplastics in Florida, United States: A Case Study of Quantification and Characterization With Intertidal Snails - Kleinschmidt, Jordan M.; Janosik, Alexis M. (Frontiers in Ecology and Evolution, 2021)
Microplastics are small particles of plastic that are five millimeters or less in size. These microscopic particles come from a variety of sources including beauty products, fishing gear, clothing, and from the degradation of plastic products. Concentrations of microplastics are increasing within the oceans, including waters surrounding Florida, USA. Miles of sandy beaches make the sunshine state a prime tourist destination leading to an increased amount of pollution along Florida coasts. Microplastics can cause damage to intertidal organisms, as well as causing issues up the food chain with biomagnification and seafood consumers, such as humans. Florida is also subject to hurricanes which often distribute sediments, filling the water column with previously settled microplastics. These factors make Florida a special case to review considering the state is affected heavily by hurricanes and tourism, which can contribute to microplastic concentrations in the Gulf of Mexico. The focus of this study was to quantify microplastics contamination in two marine snail species from intertidal habitats in Florida. The Red-mouth rock shell (Stramonita haemastoma) and Crown conch (Melongena corona) are gastropod molluscs that can be found commonly in intertidal habitats in the Gulf of Mexico. Both Red-mouth rock shells and Crown conchs are predatory snails with Red-mouth rock shells feeding on bivalves, gastropods and barnacles, while Crown conchs are predatory snails, consuming filter feeding bivalves and other snails. Marine snails serve as sustenance for other organisms in the ecosystem, such as whelks, murex, and stone crabs. If intertidal snail populations are in jeopardy as a result of microplastic contamination, ecosystem health is also at risk. Seawater samples and marine snails were collected from intertidal beach habitats in Northwest Panhandle and Central Florida, and gastropod tissue was digested for microplastic quantification. After tissue digestion was complete, seawater and tissue samples were filtered and microplastics were quantified and measured using microscopy. Marine intertidal snails may be good organisms for biomonitoring of microplastics in intertidal sandy habitats.